Case Report: Hymenolepis diminuta in an asymptomatic Ecuadorian child. [version 3; peer review: 1 approved, 2 approved with reservations] - Anita Murillo; Angela Bracho; Anthony Vera; Ader Ponce; Zulbey Rivero de Rodriguez (F1000Research)
Background The cestode Hymenolepis diminuta is a cosmopolitan parasite, which in the adult stage is usually found in the small intestine of rats and accidentally in humans. Case report We describe the finding of eggs of this parasite in an asymptomatic 3-year-old child. The child had extremely high IgE values of 1,376 IU/ml. After receiving treatment with Albendazole suspension 400mg/20mL, on the 10th day post-treatment, he showed no H. diminuta eggs in his fecal matter Conclusions Detailed morphological review of Hymenolepis nana-like eggs is recommended to distinguish them from H. diminuta eggs.